FERULA NAMANGANICA SENNIKOVI KAM UCHRAYDIGAN ENDEMIK TUR TSENO-POPULYATSIYASINING ONTOGENEZI VA ONTOGENETIK TUZILISHI (Scientific journal of the Fergana State University, 2026)
For the first time, the ontogenesis of two cenopopulations of Ferula namanganica, a rare endemic of the Fergana Valley, has been described and its ontogenetic structure has been identified. It has been shown to be a caudex perennial monocarpic herbaceous plant with a tuber-like thickening of the main root. In the development of individuals, 3 periods (latent, pregenerative, and generative) and 6 ontogenetic states have been identified. The total duration of ontogenesis is 8-10 years. The cenopopulations are full-membered, with population densities ranging from 3-5 to 0.05 individuals per m2.